Religious Barriers to Transformative Masculinity and Femininities: Church discipline on pregnant adolescent girls in the Evangelical Lutheran Church of Tanzania - Witness Issa Maratu (Pharos Journal of Theology)
Church discipline aims to correct, confront, and encourage repentance for sin with the intention of maintaining moral and spiritual integrity within the congregation. Under the category of moral delinquency, the church holds the authority to impose disciplinary measures on members proven to engage in immoral behaviours. Within the context of the Evangelical Lutheran Church in Tanzania, cases of sexual immorality and adultery are often highlighted when unmarried adult members and adolescents are found to be pregnant. While pregnancy visibly points to moral misconduct for women, equivalent indicators of immorality or adultery for men are less explicitly addressed. Furthermore, under Tanzania’s Penal Code Cap 16 2002 (R.E 2019), impregnating a girl under 18 is a criminal offense with legal implications. This paper seeks to explore religious barriers to transformative masculinity and femininities, fostering dialogue on critical concerns such as: Why are victims of sexual abuse or violence often forced to repent or prohibited from partaking in the Eucharist (frequently discovered through pregnancy)? What are the roles of the church in preventing, supporting, and responding to sexual abuse, violence, and gender-based violence? How can the church challenge unequal moral standards for men and women while equipping both to support adolescent girls and promote transformative masculinity and femininity in the face of exploitation, abuse, violence, and stigmatization?